1995
DOI: 10.1007/bf00120292
|View full text |Cite
|
Sign up to set email alerts
|

Cure behaviour of visible light activated dental composites

Abstract: During curing of multifunctional methacrylate-based composites for dental restorations, strong structural changes, significantly affecting the final properties of the materials, are observed. In fact, the polymerization of thermoset matrices involves the transformation of a viscous liquid in a glassy network. The final glass transition temperature of the composite matrix may be considered a relevant parameter for the durability of a restoration. In this study, the complex cure behaviour of a commercial dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Under these conditions, the kinetic constant of the propagation reaction, the radical efficiency and, consequently, the overall rate of reaction decrease to zero for a value of a lower than 1. This kinetic behaviour may be modelled using a simple pseudo-autocatalytic expression, obtained by modifying a kinetic equation previously proposed for free-radical polymerization of unsaturated polyester and acrylic thermosetting resins [5,13]:…”
Section: Initiation and Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the kinetic constant of the propagation reaction, the radical efficiency and, consequently, the overall rate of reaction decrease to zero for a value of a lower than 1. This kinetic behaviour may be modelled using a simple pseudo-autocatalytic expression, obtained by modifying a kinetic equation previously proposed for free-radical polymerization of unsaturated polyester and acrylic thermosetting resins [5,13]:…”
Section: Initiation and Inhibitionmentioning
confidence: 99%
“…In fact, the glass transition temperature, continuously increasing during cure, approaches the isothermal cure temperature thereby strongly reducing the molecular mobility. Under these conditions, the reaction becomes diffusion controlled and the termination step of the polymerization is governed by the strong reduction in the molecular mobility caused by vitrification [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The bulk isothermal rate of reaction model that depends on conversion has been used effectively by Maffezzoli and co-workers. 12,13 Racz et al showed that an analogy between the classical Avrami approach for phase transformations and the kinetic phenomena that occur during photocuring of polymer and copolymer resins gives rise to a simple algebraic two-parameter expression for the extent of cure versus time that matched cross-linking chemical conversion quite well.…”
Section: Introductionmentioning
confidence: 99%
“…However, most traditional kinetic models consider only the isothermal behaviour, while light curing of dental composites is a fast and highly non-isothermal bulk polymerization. The analysis of the isothermal cure of a methacrylate-based commercial dental composite, activated by visible light, presented in the first part of this study [5], has lead to the determination of very low final glass transition temperatures (Tg) in the cured parts. This result appears in contrast with the good performances shown by these materials used for dental restorations.…”
Section: Introductionmentioning
confidence: 99%